Sistema Renina-Angiotensina (SRA) e cirrose hepática - Walkiria Wingester Vilas Boas (2007)
Portal hypertension and hyperdinamic circulation represent altogether circulatory impairment of hepatic cirrhosis. Haemodinamic homeostasis is one of the major functions of RAS, that nowadays has two recognized axis: ACE/AngII/AT1 (vasoconstrictor) and ACE/Ang1-7/Mas (vasodilator). They counteract each other, determining the final function. The plasmatic profile of both RAS axis were evaluated in pre-ascites (compensated) andascites (non-compensated) phases of hepatic cirrhosis as well as its possible participation in the circulatory impairment of cirrhotic patients. The effect of oral propranolol chronic use over the plasmatic profile of ARS (splancnic and systemic) and the haemodynamics of non-compensated cirrhotic patients was observed. Methods: Healthy individuals (control group), and compensated and non-compensated cirrhotic patients were studied. At first, peripheral venous blood samples were collected to determine RAS components plasmatic levels (RPA, AngI, AngII, Ang1-7) in control group and compensated and oncompensated cirrhotic patients, taking or not oral propranolol. Later on, during preanhepatic stage of hepatic transplantation over non-compensated cirrhotic taking or not oral propranolol, haemodynamic parameters (CO,CI, SVR,SVRI) were measured and blood samples were simultaneously obtained from the portal vein and radial artery tomeasure SRA components. Results: RPA (p<0,001) and AngI (p<0,01) were augmented only in non-compensated cirrhotic. AngII was augmented in cirrhotic non-compensated (p<0,05) and reduced in cirrhotic compensated (p<0,05) compared to control. Ang1-7 wasaugmented in cirrhotic non-compensated compared to control (p<0,01) and to compensated patients (p<0,05). The final functional relation of RAS (Angio1-7/AngII) was augmented in cirrhotic compensated patients related to control (p<0,01) and cirrhotic noncompensated. Related to RAS splancnic and systemic plasmatic profile in noncompensated cirrhotics, there was a reduction of AngII (p<0,05) and elevation of Angio1- 7/AngioII relation (p<0,05) in the splancnic circulation by comparison with systemiccirculation. Haemodynamic parameters of cirrhotic patients showed elevated CO and CI, and reduced SVR and SVRI. Propranolol chronic intake by these patients reduced CO (p<0,05) and CI (p<0,05) and elevated SVR (p<0,05) and ISVR (p<0,05). Cirrhotic noncompensatedpatients showed positive correlation (r=0,66) between RAS final functional relation (Ang1-7/AngII) of radial artery and CO. Negative correlation was observed (r=-0,7) between RAS final functional relation in radial artery and SVR. Non-compensated cirrhotic patients taking propranolol showed reduction of measured RAS components in thesplancnic circulation [RPA (p<0,05), AngI (p<0,05), AngII (p<0,05), Ang1-7 (p<0,05)] and systemic circulation [RPA (p<0,05), AngI (p<0,05), AngII (p<0,05)], but without alteration in RAS final functional relation splancnic (portal vein) and peripheral. Conclusions: The plasmatic peripheral RAS is only activated during the non-compensated phase of hepaticcirrhosis. During the compensated phase there is probably inversion of predominant RAS axis toward the vasodilator (ACE/Ang1-7/Mas). During the non-compensated phase the plasmatic splancnic RAS final functional product is vasodilator in relation to the peripheral circulation. The peripheral RAS final functional relation is important in maintenance ofsystemic vascular tonus and cardiac output. Propranolol oral intake by cirrhotic noncompensated patients reduces the activation level (RPA, AngI) of RAS and its biological active peptides (AngII, Ang1-7), but do not alter its final functional relation (Ang1-7/AngII) either in the splancnic circulation or in the peripheral circulation. However, hyperdynamiccirculation is treated by propranolol use, probably due to the non-selective beta-blockade effect and not by inhibition of the RAS.